Advantages of the activity scanning approach in the modeling of complex construction processes - Martinez, Julio C.; Ioannou, Photios G. (Proceedings of the 27th conference on Winter simulation, 1995)
Construction processes are very complex and include highly interdependent components subject to complex activity startup conditions. A simulation language based on activity cycle diagrams can express the logic of complex simulation models very effectively. This paper uses Stroboscope (STate- and ResOurce-Based Simulation of COnstruction ProcEsses), a three-phase activity scanning simulation language based on extended activity cycle diagrams, to model the operations of a quarry. Although simplified, this example is representative of the complex nature of construction operations.